Fundamentals of teaching quality in the educational process (Journal of the College of Basic Education, 2022)
The teaching process aims in some of its meanings to bring about desirable changes in the behavior of the learner and to provide him with the desired information, knowledge, skills, attitudes and values, in order to achieve these educational goals that seek to bring about those desired behavioral changes. He has extensive knowledge of the various educational strategies in order to create appropriate teaching conditions for application, so that the teaching process becomes interesting and enjoyable for students, appropriate to their abilities, and closely related to their daily lives, needs, tendencies, desires, and future aspirations.